The preventive effect of Brassica napus L. oil on pathophysiological changes of respiratory system in experimental asthmatic rat - Mehdi Kabiri rad; Ali Neamati; Mohammad Hossein Boskabady; Naser Mahdavi-Shahri; Maryam Mahmoudabady (Mashhad University of Medical Sciences, 2012)
Objective: Asthma is an airway complex disease defined by reversible airway narrowing and obstruction, chronic airway inflammation, airway hyperresponsiveness, and tissue remodeling. The purpose of this study was to determine the effect of Brassica napus L. (B. napus) on airway pathologic changes in a rat model of asthma. Materials and Methods: Twenty-four rats were divided into 4 groups: control, asthmatic, asthmatic treated with 0.5 mg/kg B. napus oil, and asthmatic treated with 0.75 mg/kg B. napus oil. To induce the experimental asthma, rats in groups 2, 3, and 4 received an i.p. injection of ovalbumin and aerosolized ovalbumin. Simultaneously, rats in groups 3 and 4 received B. napus oil daily by gavage. After 31 days, in all groups, thoracotomy was done and lung tissue samples were taken. For pathological evaluation, microscopic slides were prepared. The eosinophil numbers in the submucosal layer and thicknesses of smooth muscle layer of bronchioles were detected.  Results: Eosinophil numbers in the submucosal layer, as well as smooth muscle layer thicknesses were significantly lower in the rat group treated with 0.75 mg/kg B. napus oil as compared with asthmatic group (p